Optimization and Control for Partial Differential Equations Uncertainty Quantification, Open and Closed-Loop Control, and Shape Optimization. - Herzog, Roland; Heinkenschloss, M. (Matthias); Kalise, Dante; Stadler, Georg; Trélat, Emmanuel (Radon series on computational and applied mathematics ;, 2022)
This book highlights new developments in the wide and growing field of partial differential equations (PDE)-constrained optimization. Optimization problems where the dynamics evolve according to a system of PDEs arise in science, engineering, and economic applications and they can take the form of inverse problems, optimal control problems or optimal design problems. This book covers new theoretical, computational as well as implementation aspects for PDE-constrained optimization problems under uncertainty, in shape optimization, and in feedback control, and it illustrates the new developments on representative problems from a variety of applications.